Correlation between Gleason Scores of Prostatic Biopsies and Radical Prostatectomy Specimens - Sitthinamsuwan, Panitta; Ratanarapee, Samrerng; Leewansangthong, Sunai; Senawong, Sansanee (Siriraj Medical Journal, 2009)
Objective: The incidence of prostatic adenocarcinoma in Thailand has been increasing since 1989. Increased public awareness may have contributed to early detection of the disease. Findings of abnormal digital examination, elevated serum prostate-specific antigen (PSA) level and abnormal transrectal ultrasonography (TRUS) lead to more multiple core biopsies. The Gleason grading system is the most common histologic grading of prostate carcinoma as approved by the World Health Organization. The Gleason score, one of the prognostic predictors, thus plays an important part in the therapeutic decision. The correlation between Gleason scores in biopsies and subsequent prostatectomy specimens is the main purpose of this study. Associations of Gleason scores with organ confinement, perineural invasion and serum PSA levels before prostatectomy were also studied. Methods: The specimens from 100 patients, who underwent TRUS core biopsy and subsequent prostatectomy between January 2001 and June 2004, were included. Results: Gleason grade concordance was found in 35 cases. In TRUS core biopsy, 35, 9, and 1 cases were 1, 2, and 3 scores undergraded, respectively. Thirteen and 7 cases were 1 and 2 scores overgraded, respectively. Eighty three percent show a difference of not more than 1 score. Conclusion: We concluded that the Gleason scoring in prostatic biopsy remains a good predictor of the final Gleason grading of the radical prostatectomy specimen. However, the urologists and radiotherapists should keep in mind that undergrading and overgrading in TRUS core biopsies are both possible